Pengembangan LKPD Berbasis Problem Based Learning pada Pembelajaran IPAS Materi Wujud Zat dan Perubahannya di Kelas IV - Hapsari, Rindy Yunita; Kartono, Kartono; Pranata, Rio (ISLAMIKA, 2024)
The purpose of this study was to produce Problem Based Learning-based LKPD products in IPAS learning material on the form of substances and their changes in class IV SDN 22 West Pontianak. This research uses the research and development (RnD) method with the ADDIE approach which contains four research steps, namely analysis, design, development and implementation. At the product trial stage, it was conducted in class IV SDN 22 West Pontianak with a total of 25 students. Data were collected through product validity tests by expert validators and students and teacher response questionnaires to LKPD products. The results of the material aspect validity test showed a percentage of 96% with the interpretation of “very feasible”. The results of the design aspect validity test showed a percentage of 92% with the interpretation “very feasible”. The results of the language aspect validity test showed a percentage of 95% wirh the interpretation of “very feasible”. LKPD products trials were conducted in small groups and large groups. The results of students responses in small groups showed a percentage of 91% with the interpretation of “very feasible”, while the results of students responses in large groups showed a percentage of 92% with the interpretation of “very feasible”. The results of the teacher’s response showed a percentage of 94% with the interpretation of “very feasible”. Based on the overall results of the assessment, it can be concluded that the Problem Based Learning-based LKPD product developed is very feasible to be used in the learning process of IPAS material on the form of substances and their changes in class IV SDN 22 West Pontianak.